2021
DOI: 10.1002/eat.23513
|View full text |Cite
|
Sign up to set email alerts
|

Do children with recurrent abdominal pain grow up to become adolescents who control their weight by fasting? Results from a UK population‐based cohort

Abstract: Objective Gastrointestinal (GI) problems are common in eating disorders, but it is unclear whether these problems predate the onset of disordered eating. Recurrent abdominal pain (RAP) is the most prevalent GI problem of childhood, and this study aimed to explore longitudinal associations between persistent RAP (at ages 7 and 9) and fasting for weight control at 16. Method The Avon Longitudinal Study of Parents and Children (ALSPAC) is a UK population cohort of children. Childhood RAP was reported by mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In addition to helping characterize the profile of patients diagnosed with ARFID, the present research reinforces the importance of considering weight and eating-related factors in patients with GI-related somatic symptoms ( Stein et al, 2021 ). Further research is needed to examine the extent to which eating or weight disturbances are problematic in this population, which may necessitate more proactive screening within gastroenterology and somatic symptom assessment settings.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition to helping characterize the profile of patients diagnosed with ARFID, the present research reinforces the importance of considering weight and eating-related factors in patients with GI-related somatic symptoms ( Stein et al, 2021 ). Further research is needed to examine the extent to which eating or weight disturbances are problematic in this population, which may necessitate more proactive screening within gastroenterology and somatic symptom assessment settings.…”
Section: Discussionsupporting
confidence: 66%
“…Specifically, there is a subset of patients with ARFID (∼43%) who fear aversive consequences of eating, commonly GI symptoms such as abdominal pain, dysphagia, heartburn, or nausea ( Cooney et al, 2018 ; Norris et al, 2018 ) or related to Disorders of Gut–Brain Interaction ( Murray et al, 2020 ). Furthermore, many patients with ARFID describe other physical sensations (e.g., chest pain) or related worries (e.g., fear of vomiting or choking and aversion to food textures) that may also be associated with a general heightened awareness of somatic sensations ( Fisher et al, 2014 ; Norris et al, 2014 ; Stein et al, 2021 ). SSRDs represent a related condition in which individuals present with worries about aversive somatic experiences, but in the absence of identified problems with eating (though the extent to which eating disturbances arise in SSRDs is not well documented).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with eating disorders commonly report gastrointestinal (GI) symptoms (Gibson et al, 2021;Riedlinger et al, 2020) related to disorders of gut-brain interaction (previously known as functional GI disorders; Boyd et al, 2005Boyd et al, , 2010Burton Murray, Kuo, et al, 2021;Drossman et al, 2016;Hanel et al, 2021;Wang et al, 2014;Wiklund et al, 2021), chronic GI illness (e.g., inflammatory bowel disease, celiac disease; Hedman et al, 2019;Ilzarbe et al, 2017), problems with motility (e.g., slowed colonic transit; Benini et al, 2010;Kamal et al, 1991), and/or structural GI issues (e.g., liver dysfunction; Rosen et al, 2016). GI symptoms may develop in the context of an eating disorder, may increase risk for the development of an eating disorder, or a reciprocal relationship may exist (Atkins et al, 2023;Boyd et al, 2010;Hedman et al, 2019;Stein et al, 2021). Accordingly, there is increasing interest in the GI and eating disorder intersection (Burton Murray & Staller, 2022;Chey, 2019; G. K. W. Frank et al, 2021;Peters et al, 2022;Zucker & Bulik, 2020) to inform detection, prevention, and treatment.…”
mentioning
confidence: 99%
“…In spite of findings indicating a higher prevalence of eating disorders across various chronic pain conditions including migraine headache, functional gastrointestinal disorders, fibromyalgia, and chronic facial pain [13][14][15][16][17][18], research on the overlap between eating disorders and chronic pain has been limited. One of the few studies to examine this relationship found adolescents with chronic pain and comorbid eating disorders take longer to be identified and referred for eating disorder treatment than a matched sample of adolescents without chronic pain [5].…”
mentioning
confidence: 99%